Diathermy smoke induced asthmatic attack during transurethral resection of prostate - Omodu, Ovunda Jack; George, Abiye Felix (International Surgery Journal, 2022)
The use of diathermy and other electrosurgical devices have become an indispensible and integral part of modern surgical practice. This revolutionary benefit to surgery have been associated with the release of toxic agents that represents a potential health risk. A 79 year old who had an asthmatic attack during transurethral resection of prostate (TURP) on account of benign prostate enlargement. He was a known asthmatic, incidence of attacks had become infrequent over the years, and the last asthmatic attack was over 10 years ago. Triggers for attacks were strong smell, smoke and dusty environment. He had no other systemic disease of note. The procedure was done under subarachnoid block. Thirty minutes into the procedure, he was noticed to have difficulty in breathing and coughing, there was tachycardia and elevated blood pressure. The patient oxygen saturation was between 88-92% on room air, chest auscultation revealed a wide spread rhonchi. Oxygen via a non-rebreather face mask with reservoir bag at 10L/min was commenced and intravenous hydrocortisone 200mg was given. Forty minutes into the procedure, patient’s condition did not improve. Procedure was discontinued and patient moved to the ward, patient was nebulized, intravenous aminophylline 250 mg given slowly, with repeated nebulization and continued oxygenation, patient condition improved. An immediate postoperative serum electrolyte, urea and creatinine done showed normal values to rule out TURP syndrome.